THE IMPACT OF AUTHORIZATION IN THE ASSESSMENT OF RISKS AND SAFETY MEASURES OF OVERSIZED TRANSPORT ACTIVITY - GARSTEA, Nina (Journal of Social Sciences)
The article aims to analyze the regulations and regulatory framework regarding the authorization of oversized transport, highlighting their importance in ensuring road safety and protecting the infrastructure. It also assesses the risks associated with oversized transport and implement the necessary safety measures. A descriptive and analytical approach is used, examining the doctrine in conjunction with relevant national and international legislation in the field of oversized transport. The author analyzes researchers’views, national and international normative acts that regulate the road transport of oversized goods, the conditions necessary for obtaining special transport authorizations, and the specific risks associated with these operations. The study highlights that the authorization of oversized transport is essential for preventing accidents and protecting road infrastructure. Existing regulations impose strict requirements for obtaining the Special Transport Authorization (AST), including approvals from the competent authorities and compliance with specific technical conditions. It also emphasizes assessing risks such as damage to goods, road obstacles, adverse weather conditions and proper load handling. Implementing safety measures, such as the use of properly equipped escort vehicles, is crucial to reducing the risks associated with oversized transport.